Indigenous Trichoderma harzianum as Biocontrol toward Blight Late Disease and Biomodulator in Potato Plant Productivity - Susiana Purwantisari; Harum Sitepu; Isworo Rukmi; Arina Tri Lunggani; Kadarwati Budihardjo (Biosaintifika: Journal of Biology & Biology Education, 2021)
Indigenous Trichoderma has widely used in late-blight epidemic areas in Magelang, Indonesia as biocontrol and biomodulator. But it application still lacks of scientific proof, even though it is potently to be developed. Therefore, this study aims to identify and evaluate indigenous Trichoderma application in eradicating late blight and increase productivity. This research was an experimental posttest-only using six experimental plots, with P0 plot with no treatment. The solution was made by dissolve indigenous Trichoderma solid-starter into water (m/v), then used for treatment. The treatment plots including: two groups of sprayed-only plots with doses of 100 g/ 10 L of solution for P1 and 150 g/ 10 L of solution for P2; and two group treated with sprayed-poured method using doses of 100 g/ 10 L of solution for P3 and 150 g/ 10 L of solution for P4. The positive control group was P5 group, treated using chemical pesticides and tuber booster. The microscopic identification revealed that the local bioagent was Trichoderma harzianum species. Application of T. harzianum in P4 was significantly increased the productivity. However, it was not effective in increasing growth, but able to reduce the intensity of late blight disease. The research revealed that native Trichoderma is able to be used as anti-infectious agent and potentially improve the quality of potato plants. In the future, this research may worthwhile for farmers to develop and produce trustworthy and proven Trichoderma-based biocontrol and help them increase the potato production economically.